Impact of Ocean Acidification on the Intestinal Microbiota of the Marine Sea Bream (Sparus aurata L.) - Fonseca, Filomena; Cerqueira, Ricardo; Fuentes, Juan (Frontiers in Physiology, 2019)
Within a scenario of increasing atmospheric CO2 and ocean acidification (OA), it is highly relevant to investigate its impacts not only on fish performance but also on fish intestinal microbiome and how that reflects on host performance and health. The main objective of this study was to establish if the intestinal microbiota of the sea bream (Sparus aurata) was affected by high level of CO2 in line with the predictions for this century. The bacterial communities of the intestinal fluid were characterized in animals kept at the present-day level of CO2 (400 μatm) and in animals switched to high CO2 (1200 μatm) for one month. Bacterial taxa identification was based on molecular methods, using the DNA coding for the 16S ribosomal RNA and primers targeting the regions V1 to V3. Amplicons obtained from DNA samples of animals in the same tank were combined, cloned to obtain a bacterial DNA library, and the clones were sequenced. No significant differences were found between the two treatments for alpha diversity. However, beta diversity analysis revealed distinct dysbiosis in response to hypercapnia, with phylum Firmicutes absent from the bacterial communities of fish exposed to 1200 µatm CO2, whereas Proteobacteria relative abundance was increased at elevated CO2, due to the presence of Gammaproteobacteria (Vibrionaceae and Alteromonadaceae), a class not present in the control samples. This study provides a first glimpse at the impact of ocean acidification in fish intestinal microbiota and highlights potential downstream effects to the general condition of fishes under hypercapnia.